Review of sun exposure guidance documents in Australia and New Zealand - Christina Verma; Jessica Lehane; Rachel E Neale; Monika Janda (Sax Institute, 2022)
Importance: Exposure to ultraviolet (UV) radiation from the sun has both risks, including skin cancer and premalignant lesions, skin aging and cataracts, and benefits, including the production of vitamin D. Health policies guide informed decision making about balancing these risks and benefits. However variability in advice given by different agencies (e.g. government, health organisations, consumer organisations) may lead to confusion among the general public, resulting in suboptimal health-related behaviours by consumers. Objective: To review and assess the consistency of recommendations in relevant guidance documents in Australia and New Zealand regarding the risks and benefits of sun exposure. Study type and methods: A rapid desktop review of publicly available sun exposure guidance documents from government and nongovernment websites was undertaken between February and April 2021. Four major themes and their subthemes were extracted from documents: sun protection; balance between risks and benefits of sun exposure; non-vitamin D benefits of sun exposure; and sun exposure and vitamin D production. We then undertook a more detailed analysis of recommendations regarding sun exposure to maintain sufficient vitamin D status. Results: Nineteen documents met the inclusion criteria (13 Australian, five New Zealand, and one joint Australian and New Zealand document). Most documents provided extensive advice about sun protection and sun exposure and vitamin D production and their respective subthemes, while only 2/19 documents provided advice regarding the non-vitamin D benefits of sun exposure (benefits for melatonin production and reduction of sleep disorders). Documents varied widely in their recommendations in relation to sun exposure required for vitamin D production. For example, while three documents stated that sun exposure is required on most days of the week for adequate vitamin D production, two stated that sun exposure is required daily. One document advised that people with darker skin require three to six times more sun exposure than those with lighter skin, while another advised two to three times more sun exposure is required. Conclusion: Current guidance documents show great variation in the advice for sun exposure and vitamin D production, and little advice is being provided on non-vitamin D health benefits. Extensive variations in the advice provided could be confusing for consumers and result in unhealthy behavioural action. Based on this evidence, better and more consistent guidance and advice about the risk and benefits of sun exposure is required.